Reframing place-based economic development in South Africa: the example of local economic development - Rogerson Christian M. (Bulletin of Geography. Socio-Economic Series)
Local Economic Development (LED) planning is a place-based approach to development planning and increasingly significant across much of the global South. One of the key challenges facing LED planning is the necessity to adjust planning in relation to the dynamic nature of both international and national framework conditions. The purpose of this article is to show this challenge by examining the dynamic nature of the national policy environment impacting upon LED planning in South Africa, a country which has a relatively long history of LED planning. Five dimensions of the changing landscape of national economic development planning in South Africa are identified. These relate to (a) LED within the context of new national economic and development plans; (b) initiatives for reindustrialising the South African economy, the associated importance of localisation and promotion of the green economy; (c) changing programmes around small business development; (d) shifts in rural development interventions; and (e) the fluid spatial context within which LED planning as a form of placebased economic development is embedded.